2018
DOI: 10.1096/fj.201700962r
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JAK/STAT3 restores NK‐cell function and improves immune defense after brain ischemia

Abstract: Stroke-induced immune suppression predisposes the host to infections and can contribute to high morbidity and mortality in stroke patients. Because ischemic stroke has a profound effect on the systemic immune response, which may explain the increased susceptibility of stroke patients to infection, an urgent need persists for a better understanding of mechanisms associated with immune suppression; new and effective treatments for stroke can then be identified. NK cells play a key role in early host defense agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…These findings provide clues to further clarify the immunosuppressive mechanism of human NK cells. Consistent with previous studies showing impaired NK cell response after stroke (4,22), these findings suggest that miR-451a and miR-122-5p are possibly involved in the alteration in expression of NK cell surface markers CD69 and NKG2D, but whether miR-451a and miR-122-5p contribute to strokeinduced NK cell deficit needs to be further confirmed by NK cell functional assays.…”
Section: Discussionsupporting
confidence: 89%
“…These findings provide clues to further clarify the immunosuppressive mechanism of human NK cells. Consistent with previous studies showing impaired NK cell response after stroke (4,22), these findings suggest that miR-451a and miR-122-5p are possibly involved in the alteration in expression of NK cell surface markers CD69 and NKG2D, but whether miR-451a and miR-122-5p contribute to strokeinduced NK cell deficit needs to be further confirmed by NK cell functional assays.…”
Section: Discussionsupporting
confidence: 89%
“…The expression and dysregulation of immune-related genes (IRGs) are involved in the regulation of the immune system. The activation of the JAK/STAT3 signaling pathway restores natural killer cell function and improves immune defense after cerebral ischemia (Jin et al, 2018). A related study found that galectin-1 restores immune tolerance to liver transplant patients by activating hepatic stellate cells (Jiang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various immune cells including T cells, B cells, NK cells, and macrophages have been shown to be involved in stroke-induced neuroinflammation. [3][4][5] Among these cell types, macrophages vastly outnumber all other leukocytes in the ischemic brain. They receive signals from other leukocytes as well as affect other leukocytes by releasing inflammatory factors, thus they are a central player in stroke-induced neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%